Lower Expression of Ndfip1 Is Associated With Alzheimer Disease Pathogenesis Through Decreasing DMT1 Degradation and Increasing Iron Influx - Tian, Juan; Zheng, Wei; Li, Xin-Lu; Cui, Yuan-Hong; Wang, Zhan-You (Frontiers in Aging Neuroscience, 2018)
We have previously reported that high expression of divalent metal transporter 1 (DMT1) plays a crucial role in iron dyshomeostasis and β-amyloid (Aβ) peptide generation in the brain of Alzheimer's disease (AD). Recent studies have shown that Nedd4 family interacting protein 1 (Ndfip1) can degrade DMT1 through ubiquitination pathway, and reduce the accumulation of intracellular iron. The present study aims to evaluate whether Ndfip1 is involved in AD pathogenesis through mediating DMT1 degradation and iron metabolism. APP/PS1 transgenic mouse and Ndfip1 transfected SH-SY5Y cells were used in this study. Immunohistochemistry and Western blot were performed to examine the distribution and expression levels of Ndfip1 and DMT1. In addition, ELISA and calcein fluorescence were carried out for analyzing the levels of Aβ peptide and iron influx, respectively. The results showed that Ndfip1 immunoreactivity was decreased in the cortex and hippocampus of APP/PS1 mice, compared with wild type controls. Colocalization of Ndfip1 and Aβ within senile plaques could be observed. Immunoblot analyses showed that low expression of Ndfip1 and high expression of DMT1 proteins were detected in APP/PS1 mouse brain, compared with age-matched wild type animals. Overexpression of Ndfip1 down-regulated DMT1 expression, and reduced iron influx and Aβ secretion in SH-SY5Y cells. Further, overexpressed Ndfip1 significantly attenuated iron-induced cell damage in Ndfip1 transfected cells. The present study suggests that lower expression of Ndfip1 might be associated with the pathogenesis of AD, through decreasing DMT1 degradation and increasing iron accumulation in the brain.